2008
DOI: 10.1117/1.2978062
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication strategies and potential applications of the “green” microstructured optical fibers

Abstract: Biodegradable microstructured polymer optical fibers have been created using synthetic biomaterials such as poly(L-lactic acid), poly(epsilon-caprolactone), and cellulose derivatives. Original processing techniques were utilized to fabricate a variety of biofriendly microstructured fibers that hold potential for in vivo light delivery, sensing, and controlled drug-release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Another incorporated fabrication process with co-rolling of plastic films, powder-filling and solution-casting has been investigated to manufacture fibers with functionalized hollow microstructures [ 30 ]. Particularly, microstructured fibers with functionalized hollow microstructure can be used in vivo for real-time detection of biomolecule binding events.…”
Section: Biocompatible Optical Waveguidesmentioning
confidence: 99%
See 3 more Smart Citations
“…Another incorporated fabrication process with co-rolling of plastic films, powder-filling and solution-casting has been investigated to manufacture fibers with functionalized hollow microstructures [ 30 ]. Particularly, microstructured fibers with functionalized hollow microstructure can be used in vivo for real-time detection of biomolecule binding events.…”
Section: Biocompatible Optical Waveguidesmentioning
confidence: 99%
“…Step-index fibers with multicore can be used in vivo for fluorescence microscopy by delivering high power light in a smaller core and collecting fluorescence in a larger core with higher numeric aperture (NA). Finally, the in-vivo direct use of biopolymer optical fibers promises a more compact alternative to endoscopes [ 30 ]. Figure 2 d shows the transmitting light profiles of the diverse cross-sections of cellulose-based fibers.…”
Section: Biocompatible Optical Waveguidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers have already fabricated free-standing films with mesoporous structures using CNCs as templates for the applications including catalysis, separation and sensing [23,24]. Simultaneously, other cellulose derivatives were doped into the microstructured optical fibers to increase the sensitivity of sensor probe or for imaging in vivo [25][26][27]. Sahcear et al reported a new strategy to build large-scale solvent-responsive elastomeric opal films, in which hard-soft coreinterlayer-shell (CIS) beads were used to prepare paper-supported elastomeric opal films with remarkably distinct iridescent reflection colors.…”
Section: Introductionmentioning
confidence: 99%